Between improvisation and inevitability: former Latvian officials' memoirs of the Soviet era. Issue 4 (1st October 2016) - Kaprāns, Mārtiņš
ABSTRACT: This article deals with the autobiographies of former Soviet officials that have been published in Latvia since the 1990s. In particular, it focuses on three interrelated layers of biographical narrative: construction of social identity, strategies for avoiding the stigmatization of collaboration, and comparisons between the Soviet and post-Soviet experience. The article contends that former officials in their memoirs use a pragmatic representation of the Soviet past as the major locus of their positive identity. Through this genuine representation of the past, autobiographers emphasize virtues that might be accepted by a post-Soviet neoliberal society.